Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
By solving the formula P = 2l + 2w for w yields:
w = (P - 2l)/2
To solve the formula P = 2l + 2w for w means to make w the subject of the formula from P = 2l + 2w.
Since we have;
- P = 2l + 2w
We need to subtract 2l from both sides of the equation so that we have;
- P - 2l = 2w
We need to divide both sides by 2 so that we have;
- w = (P - 2l)/2
Ultimately, solving the formula P = 2l + 2w for w yields; w = (P - 2l)/2
Read more:
https://brainly.com/question/4694454
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.